Experiências e sentimentos relacionados a cuidado de crianças com diabetes mellitus tipo 1. - Barbosa, Kamilla Arruda (2016)
The establishment of the diagnosis of infant diabetes mellitus is always accompanied by varied conditions of suffering and expectations on the child and in the whole family, determining intense changes in their lives. Not only because of the disease itself, but also for all the emotional, social, affective, spiritual and cultural repercussions that involves, more and more, as well as family dynamics and even the clinician-patient relationship, associated to control the disease. The aim of this study was to understand the experience and repercussions of care of children with diabetes mellitus type 1 in the view of the mothers or guardians. The field was developed in a Clinic of Medical Specialties of the municipal SUS of Santos-SP. It is a study of qualitative approach with semi structured interviews with mothers or caregivers as the principal source of evidence. As an initial and exploratory study, the specific clinical categories of the medical field were purposely excluded. The results evidence the continuous exposure of these mothers and caregivers to conflicts and complex situations in everyday life of the care of diabetic children, whose abrupt and intensive beginning of exposure starts immediately with the diagnosis. Situations dating back to perceived experiences of superficiality of professional guidance initially made available; in supporting the impact of the diagnosis that usually is repeated in all phases of the course of the disease. The difficulties the school environment to address the specific needs of the child are widely reported. In conclusion, crops out the importance of improving the knowledge and professional training, whether in health system, whether at school environment, for the full care of diabetes mellitus child carrier.